دراسة بيولوجيا التكاثر والخصوبة عند الرخوي Strombus persicus (Sowerby,1842) في شاطئ اللاذقية (Gastropoda: Strombidae) - صقر, فائز; ناصر, أميمة; صبحة, علي (Latakia University Journal -Biological Sciences Series, 2019)
The research determination, for the first time, with studying the absolute and relative fecundity, The identification of reproductive times and developmental stages of both ovaries and testes of Gastropod Strombus persicus in the shore of Lattakia. This research was achieved between March 2016 to February 2017 at Afmia area from Lattakia shore, the shell length varied between 3.43 and 6.47 cm, while the total weight 9.12 and 24.2 g, the absolute fecundity varied between 1.052 and 3.661 million egg, and between 0.829 to 2.753 million egg/g body weight for relative fecundity, all the correlation relationships were positive and solid, while spawning took place from mid-May to the end of October, with peak during August. Five stages were determined for gonadal development (ovaries or testises), respectively: inactive, developing, mature, partially spawned, spent. تناول هذا البحث لأول مرة دراسة الخصوبة المطلقة والنسبية، وتحديد أوقات التكاثر، ومراحل تطور المبايض والخصى عند بطني القدم Strombus persicus في شاطئ مدينة اللاذقية. نفذ هذا البحث خلال الفترة من آذار 2016 وحتى شباط لعام 2017، في منطقة أفاميا من شاطئ مدينة اللاذقية، تراوحت أطوال القوقعة ما بين 6.47 و 3.43 سم، و الوزن الكلي 24.2 و 9.12 غ، تراوحت قيمة الخصوبة المطلقة ما بين 1.052 و3.661 مليون بيضة والخصوبة النسبية ما بين 0.829 و2.753 مليون بيضة /غ من وزن الجسم، وكانت جميع علاقات الإرتباط إيجابية وموثوقة، أما وضع البيض فحدث خلال الفترة الممتدة من منتصف شهر أيار إالى نهاية تشرين الأول والذروة خلال شهر أب. حددت خمس مراحل لتطور المنسل (المبايض أو الخصى) عند الإناث والذكور هي بالترتيب: الخمول، التطور أو التنامي و النضج و الوضع الجزئي للبيض و الإنهاك أو التلاشي.